2012
DOI: 10.1093/humrep/des318
|View full text |Cite
|
Sign up to set email alerts
|

Live birth rates following natural cycle IVF in women with poor ovarian response according to the Bologna criteria

Abstract: No funding was used. There are no competing interests to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 16 publications
5
72
3
3
Order By: Relevance
“…The results of our current analysis cannot easily be compared to most other studies involving poor responders, as the definition of poor responders is inconsistent among these. However, there are two more recent studies which use these latest Bologna criteria to evaluate natural cycle IVF treatment in poor responders [18,19]. The earlier one by Polyzos et al [18] concludes that poor responders do not respond well to natural cycle IVF, with ongoing pregnancy rates per cycle under 3 % in all age groups in this category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our current analysis cannot easily be compared to most other studies involving poor responders, as the definition of poor responders is inconsistent among these. However, there are two more recent studies which use these latest Bologna criteria to evaluate natural cycle IVF treatment in poor responders [18,19]. The earlier one by Polyzos et al [18] concludes that poor responders do not respond well to natural cycle IVF, with ongoing pregnancy rates per cycle under 3 % in all age groups in this category.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the Bologna criteria for poor ovarian response were established [17] to make it possible to compare different studies on this subject. Following this, a retrospective cohort trial [18] comparing poor responders, defined by the Bologna criteria, to normal responders in natural cycle IVF showed contradictory results to the studies previously stated. Also, a recent study looking at outcomes of mnIVF in poor responders, with a protocol very similar to the one used in our center, showed that this treatment yields poor outcomes in this patient population [19].…”
Section: Introductionmentioning
confidence: 86%
“…The review by Polyzos et al [14] suggested that pregnancy outcome in poor responder women undergoing the natural IVF were substantially low with a positive HCG rate of 4.6 % and live birth of 2.6 % per cycle. On the other hand, the study of Jonsdottir et al [54] confirmed that the live birth rate in poor responders after double embryo transfer was clinically and statistically significantly higher than after single embryo transfer with a modest increase in multiple birth rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pregnancy rate per started cycle have been observed to be relatively low (0-18.3 %) [2,3,14,[21][22][23][24]. The cumulative pregnancy rate in the population of normal responders was estimated about 20.8 % [3] and 44 % [4] only after three and nine cycles, respectively.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation